Spain's Foreign Trade and Trade Policy in The Period 2014-2019 - Ovidiu Andrei Cristian BUZOIANU; Amelia DIACONU; Florin DOBRE; Cristina DIMA; Oana Matilda SABIE (Communications of International Proceedings, 2021)
Trade in goods and services makes a significant contribution to boosting sustainable growth and job creation. More than 30 million jobs in the EU depend on exports outside the EU. This article makes a detailed analysis of the state and evolution of Spain's foreign trade activity in the period 2014-2019, as well as of the aspects related to the trade policy of the European Union, with a particularization for Spain. The emphasis is generally on the evolution of phenomena in recent years. The aim of the paper is the in-depth research of the economic branches, foreign trade and trade policy of Spain. The objectives of this paper are: general presentation of Spain, analysis of macroeconomic indicators, study of economic branches, analysis of the value of foreign trade and trade balance, study of imports and exports, study of trade policy and formulation of conclusions.
Keywords: commerce; exports; GDP imports; Spain